Conflict between morphological and molecular data: A case study of Ficus krishnae (Moraceae) - Anand, Kumar K.; Jena, Satya N.; Chaudhary, Lal B.; Singh, Munna (Phytotaxa, 2016)
Ficus krishnae, considered as highly sacred plant species in India, is well known for its peculiar nature of cup-shaped leaves. The species distinctly differs from its allied species F. benghalensis not only in the cup formation in leaves but also in the height of plants, aerial roots, stipules, petiole and its leafy appendages, ostiolar bracts of the receptacle and pollinator wasps, in addition to slight differences in the karyotype, DNA contents, stomatal and parenchymatous cells and nodal anatomy. In spite of having several morphological differences, F. krishnae is considered by some authors as a synonym of F. benghalensis, which does not seem to be convincing. Contrary to the morphological differences, the sequence analysis of nuclear and plastid regions of both the species conducted in the present study does not reveal any significant variations and thus infers no differentiation between the species at molecular level. This may be due to mutations at one or few coding loci or differences in gene expression associated with morphogenesis with significant phenotypic appearance.